Pengaruh konsultasi gizi terhadap asupan karbohidrat dan kadar gula darah pasien Diabetes Mellitus Tipe II di Poliklinik Endokrin RSUZA Banda Aceh - Nunung Sri Mulyani (Politeknik Kesehatan Kemenkes Aceh, 2019)
Background: Wasting is nutritional status in school children. In the community it is known as thin nutrition which is an important public health problem because it has a big impact. Thin nutrition can increase the risk of illness and death in children Diabetes Mellitus is a disorder of carbohydrate metabolism caused by a deficiency of insulin released by the pancreas gland both relative and absolute. In addressing the prevalence of Diabetes Mellitus in the Regional General Hospital dr. Zainoel Abidin Banda Aceh held nutritional consultations in outpatients and inpatients aimed at making changes to the knowledge, attitudes, and behavior of patients' eating patterns. In Aceh, in 2016 the number of Diabetes Mellitus patients was 29% and increased in 2017 by was 30%.Objectives: To determine the effect of nutritional consultation on carbohydrate intake and blood sugar levels in Type II Diabetes Mellitus patients.Methods: This type of research is descriptive analytic, sampling is done by purposive sampling and obtained 30 samples. This research was conducted in June 2017 at in Endocrine Polyclinic of RSUZA hospital Banda Aceh. The data taken are primary and secondary data. Data collection by interview using a questionnaire, food recall with interview techniques and examination of blood sugar levels before and after consultation. Data analysis uses T-Dependent Test (Paired Sample T-Test) with SPSS.Results: The results showed that there were significant differences in carbohydrate intake between before and after nutrition consultations were given in patients of Diabetes Mellitus Type II with a p-value= 0.001. Blood sugar level also shows the difference between after being given a nutrition consultation with a value of p-value= 0.000 in patients of Diabetes Mellitus Type II in the in Endocrine Clinic of RSUZA hospital, Banda Aceh.Conclusion: Nutrition consultation has a significant effect on carbohydrate reduction and blood sugar levels in patients with Diabetes Mellitus Type II in the Endocrine Polyclinic of RSUZA Banda Aceh. Keywords